2019
DOI: 10.3102/0002831219862998
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immigration Enforcement on the Nation’s Schools

Abstract: In response to growing concerns about the impact of harsh immigration enforcement policy since the 2016 presidential campaign, we examined its overall impact on the nation’s schools, using survey data completed by over 3,600 educators across the country. Our study results show that immigration enforcement is affecting all students—both those from immigrant homes and those that are not. In particular, Title I schools are the most affected by immigration enforcement. Our results also show that the higher the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 31 publications
5
93
0
2
Order By: Relevance
“…Furthermore, a recent study surveyed educators nationally and found that 85% of participating teachers and administrators reported observing explicit indications of fear of immigration enforcement among immigrant children—even though most of the children were US citizens. Researchers also found that Title I schools with larger shares of English learners (ELs) and schools with higher proportions of White students were more likely to experience more pronounced negative effects associated with immigration enforcement (e.g., absenteeism, increased student emotional and behavioral concerns, bullying) (Ee & Gándara, 2020). The latter finding that teachers in schools with more White students reported more salient negative effects of immigration enforcement appears to bolster previous research documenting increasing polarization and belligerence toward racially minoritized students in majority‐White schools (Ee & Gándara, 2020).…”
Section: Research On the Impact Of Immigrant Detention And Family Sepmentioning
confidence: 99%
“…Furthermore, a recent study surveyed educators nationally and found that 85% of participating teachers and administrators reported observing explicit indications of fear of immigration enforcement among immigrant children—even though most of the children were US citizens. Researchers also found that Title I schools with larger shares of English learners (ELs) and schools with higher proportions of White students were more likely to experience more pronounced negative effects associated with immigration enforcement (e.g., absenteeism, increased student emotional and behavioral concerns, bullying) (Ee & Gándara, 2020). The latter finding that teachers in schools with more White students reported more salient negative effects of immigration enforcement appears to bolster previous research documenting increasing polarization and belligerence toward racially minoritized students in majority‐White schools (Ee & Gándara, 2020).…”
Section: Research On the Impact Of Immigrant Detention And Family Sepmentioning
confidence: 99%
“…These include federal law regarding children’s right to education regardless of documentation status, state-level policies about the extent to which immigrants are included in state welfare programs, and school-level policies about how teachers engage and instruct the children of immigrants and their families (Filindra et al 2011; Golash-Boza and Valdez 2018; Portes and Rumbaut 2014). For instance, on one hand, schools can also play a positive role in engaging immigrant families and their children through several channels, such as developing culturally responsive events, creating communicative bridges with families, and supporting a schoolwide recognition of the unique assets newcomer students and their families bring; on the other hand, schools can also have a negative role in engaging immigrant families and their children through many channels, such as restricted access to educational opportunities and extracurricular activities, implementing stringent surveillance and punishment policies or practices, and sustaining an anti-immigrant climate of harassment and biased treatment (Durán 2013, 2018; Ee and Gándara 2020; Garver and Noguera 2015; Kao et al 2013; Peguero 2009, 2011; Peguero and Bondy 2015, 2020; Peguero and Shekarkhar 2011; Rios 2011, 2017). What remains unknown, however, is the association between the schools’ context of reception and crime for the children of immigrants.…”
Section: Immigration Race/ethnicity Context Of Reception and Schoolsmentioning
confidence: 99%
“…Second, considering the school context, school is a place where deviance, violence, and crime could be conveyed by students who are interacting with well-behaved or misbehaved students. The children of immigrants are more likely to attend marginalized and disadvantaged schools with increased levels of disorder, discrimination, and diminished educational resources (Ee and Gándara 2020; Garver and Noguera 2015; Gonzales 2016; Kao et al 2013; Peguero and Bondy 2015). Thus, misbehavior may be normative and part of the school’s environment or contextual climate and influence the behavior and exposure to disorder and violence of children of immigrants.…”
Section: Immigration Race/ethnicity Context and School Crimementioning
confidence: 99%
“…Inattention to disparities in the early grades can lead to higher levels of high school dropout and lower instances of postsecondary attainment (Gándara & Mordechay, 2017), while Latinxs who do receive support have higher GPAs and are more likely to attend college (Bordes-Edgar et al, 2011). Discrimination against Latinx students has been a constant over the last century, but has increased substantially since the 2016 election: school principals report an increase in anxiety over immigration policies targeting Latinx families, creating deleterious effects on students' health and well-being (Ee & Gándara, 2020). While not the only racial/ethnic group affected by poverty and linguistic isolation, Latinx students are the largest minority group, and their treatment has implications for other groups experiencing marginalization.…”
Section: Triple Segregationmentioning
confidence: 99%